Competition between meiotic and apomictic pathways during ovule and seed development results in clonality - Hojsgaard, Diego Hernán (2013)
Fil: Hojsgaard, Diego Hernán. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.